Pojęcie i zakres zakładowej działalności socjalno-kulturalnej - Piwosz, Jerzy (Wydział Prawa i Administracji UAM, 1978)
The development of social and cultural activities is connected not only with the increase in number of institutions meant for serving these activities but also with the development of their organizational forms and financial norms. Among the aforementioned activities those operating in enterprises have been developing in a particularly rapid way in the recent years. On the one hand there are arguments against this development, demanding a reduction in the scope of social and cultural services pointing to their relatively high costs and insufficient utilization. However, these arguments refer only to those aspects of the social and cultural services which are connected with the organizational costs of the relevant facilities in enterprises. But the social and cultural services can be implemented also by way of hiring the services from public social and cultural institutions or could be introduced to the enterprises by social organizations. On the other hand, there are many substantial arguments for maintaining and further developing the social and cultural services operating in enterprises. These arguments are, among others, connected with the basic functions of the enterprises. Taking all the above into consideration, in the article the author selected certain criteria according to which the scope of social and cultural services organized in enterprises could be determined.
The Idea and Scope of Social and Cultural Activities in Enterprises